2554. Safety and Immunogenicity of NasoVAX, a Novel Intranasal Influenza Vaccine. (26th November 2018) - Tasker, Sybil; Krishnan, Vyjayanthi; Bart, Stephan; Suyundikov, Anvar; Booth, Peta-Gay; Wight O'Rourke, Anna; Zhang, Jianfeng; Georges, Bertrand; Roberts, Scot
Abstract: Background: NasoVAX is a replication-deficient adenovirus-based vaccine designed to express influenza hemagglutinin in nasal epithelial cells when given as a nasal spray. In preclinical studies, NasoVAX was associated with divergent strain protection. Prior preclinical and clinical studies with the vector demonstrated lack of impact from baseline adenovirus immunity. Methods: Sixty healthy adults were randomized to an A/California 2009-based monovalent NasoVAX formulation at doses of 10 9, 10 10, or 10 11 viral particles or saline placebo, all given as a 0.25 mL nasal spray in each nostril. Subjects were followed for safety, including solicited local and systemic side effects. Immune measures included hemagglutination inhibition (HAI) and neutralizing antibody (MN) at days 1, 15, 29, 90, and 180, and γ-interferon ELISpot at day 1 and 8. A parallel cohort of 20 similar subjects were dosed with Fluzone® injectable influenza vaccine containing an A/California 2009 component and had assessments at the same timepoints. The laboratory was blind to treatment assignment for these comparator samples. Results: NasoVAX was well tolerated with no serious adverse events and no fever. Solicited symptoms such as nasal congestion, sore throat, and headache did not increase with dose and were not statistically different than placebo. Available immune response data are shown below. Conclusion: NasoVAX intranasal influenza vaccine was well tolerated and elicited comparable antibody responses and nearly 6-fold higher cellular immune responses than a licensed injectable vaccine. Disclosures: S. Tasker, Altimmune, Inc: Employee and Shareholder, Salary. V. Krishnan, Altimmune, Inc.: Employee and Shareholder, Salary. S. Bart, Altimmune, Inc.: Research Contractor, fee for research services. A. Suyundikov, Altimmune, Inc.: Employee, Salary. P. G. Booth, Altimmune, Inc.: Research Contractor, fee for research services. A. Wight O'Rourke, Altimmune, Inc.: Employee and Shareholder, Salary. J. Zhang, Altimmune, Inc.: Employee and Shareholder, Salary. B. Georges, Altimmune, Inc.: Employee and Shareholder, Salary. S. Roberts, Altimmune, Inc.: Employee and Shareholder, Salary.